2016
DOI: 10.1002/bies.201600002
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the motor protein upon attachment: Anchors weigh in on cytoplasmic dynein regulation

Abstract: Cytoplasmic dynein is the major minus-end-directed motor protein in eukaryotes, and has functions ranging from organelle and vesicle transport to spindle positioning and orientation. The mode of regulation of dynein in the cell remains elusive, but a tantalising possibility is that dynein is maintained in an inhibited, non-motile state until bound to cargo. In vivo, stable attachment of dynein to the cell membrane via anchor proteins enables dynein to produce force by pulling on microtubules and serves to orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 114 publications
(196 reference statements)
0
13
0
Order By: Relevance
“…Since only LIN-5 is strictly required for cortical pulling force generation, the question arises why a tripartite dynein anchor is conserved from worm to man. In yeast, dynein is localized by the single-component cortical anchor Num1, a coiled-coil domain protein with a PH-domain for membrane localization (Ananthanarayanan, 2016). Our ectopic ePDZ-LOV heterodimerization experiments show that membrane-tethered LIN-5 could suffice as a dynein anchor and activator, and that local regulation is needed to rotate and migrate the spindle.…”
Section: Discussionmentioning
confidence: 78%
“…Since only LIN-5 is strictly required for cortical pulling force generation, the question arises why a tripartite dynein anchor is conserved from worm to man. In yeast, dynein is localized by the single-component cortical anchor Num1, a coiled-coil domain protein with a PH-domain for membrane localization (Ananthanarayanan, 2016). Our ectopic ePDZ-LOV heterodimerization experiments show that membrane-tethered LIN-5 could suffice as a dynein anchor and activator, and that local regulation is needed to rotate and migrate the spindle.…”
Section: Discussionmentioning
confidence: 78%
“…This is an intriguing possibility as mitochondria and dynein both interact with the CC domain of Num1 [1012]. In addition, Num1 is proposed to directly activate dynein [18,19,28]. Thus, the mitochondria-dependent arrangement of Num1 within a cluster may also impact the ability of Num1 to activate dynein.…”
Section: Discussionmentioning
confidence: 99%
“…Cluster formation has been proposed to enhance the interaction between Num1 and its membrane and protein binding partners and, consequently, the ability of Num1 to robustly tether mitochondria and dynein to the cell cortex [10,11]. In addition, Num1 is proposed to directly activate dynein [18,19]. Thus, increasing the effective concentration of Num1 via cluster formation may also enhance dynein activation at sites of anchoring.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that MT-based cytoskeleton that appears as tracklike structures is working in concert with MT-specific motor proteins (e.g., dynein 1) to support the transport of cargoes across mammalian cell cytosol, including mitochondria, chromosomes, and numerous cell organelles (4,5,8,12,59). Thus, when the heavy chain of cytoplasmic dynein 1, a minus-end-directed MT motor complex, namely Dync1h1, was silenced in the testis in vivo, it impeded the transport of developing spermatids and other cellular organelles, such as residual bodies and phagosomes, across the seminiferous epithelium during the epithelial cycle to support spermatogenesis and cell polarity.…”
Section: Discussionmentioning
confidence: 99%